Delone McLean Model Application for RGIS User Satisfaction‎Assessment in Regional Government - Nasution, Anggi Pratama; Erlina; Sirojuzilam; Muda, Iskandar (International Journal of Accounting and Economics Studies, 2025)
User satisfaction models developed for voluntary technology adoption may not adequately explain outcomes in mandatory government ‎system implementations. This study extends the DeLone-McLean information systems success model to mandatory usage contexts by ‎examining determinants of user satisfaction with Indonesia’s Regional Government Information System. Data from 155 government ‎officials using RGIS for planning, budgeting, and reporting were analyzed using structural equation modeling. Results demonstrate that ‎perceived usefulness (β = 0.567, p < 0.001) substantially outweighs system quality (β = 0.284, p < 0.001) in predicting satisfaction, ‎explaining 52.3% of variance. This dominance of functional benefits over technical attributes in mandatory contexts extends existing theory ‎and suggests government digital transformation strategies should prioritize usefulness enhancement over system quality improvements. The ‎findings provide empirical evidence for resource allocation decisions and advance understanding of information systems success in ‎developing country government settings‎.